KNOWLEDGE OF BREASTFEEDING TECHNIQUES AMONG PRIM GRAVID WOMEN - Sriyatin S; Ninda Lutfiani (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2018)
The Indonesian health research data (Riskesdas) in 2010 showed that the percentage of mothers who breastfeed their baby were low especially Exclusive Breastfeeding. The percentage of infants who get exclusive breastfeeding was only 15.3%. Factors that affect mothers not giving breast milk to their babies include limited knowledge about the benefits of breast milk and breastfeed techniques. Bojonggebang village had the lowest coverage of exclusive breastfeeding in Babakan District in 2015. The purpose of this study was to determine the level of knowledge of primipara women about breastfeeding techniques. This research was a descriptive quantitative study. The number of samples was 40 post-partum women who selected by the total sampling technique. The sample criteria were prim gravid women, breastfeed their baby, living in the village of Bojonggebang, and willing to become respondents. Data collection was conducted from May 30 to June 4, 2016 using a questionnaire containing data on maternal demographics, and knowledge about breastfeeding techniques. The results showed that the majority of respondent were 20-34 years old (97.5%), and had basic education (65.0%). Most mothers have limited knowledge of breastfeeding techniques (82.5%). There were women who had a baby before 20 years old, and most women who participated in this study only attending the basic education. These two characteristics increase the health risks of women and their babies. Health education, and counseling programs are needed for prim gravid women to support their health.Keywords: Breastfeeding techniques, knowledge, prim gravid